Description of Various Factors Contributing to Traffic Accidents in Youth and Measures Proposed to Alleviate Recurrence - Gicquel, Ludovic; Ordonneau, Pauline; Blot, Emilie; Toillon, Charlotte; Ingrand, Pierre; Romo, Lucia (Frontiers in Psychiatry, 2017)
Traffic accidents are the leading cause of hospitalization in adolescence, with the 18 to 24 years old age group accounting for 23% of deaths by traffic accidents. Recurrence rate is also high. One in four teenagers will have a relapse within the year following the first accident. Cognitive impairments known in adolescence could cause risky behaviors, defined as repetitive engagement in dangerous situations such as road accidents. Two categories of factors seem to be associated with traffic accidents: 1) factors specific to the traffic environment; and 2) "human" factors, which seem to be the most influential. Moreover, the establishment of a stronger relation to high speed driving increases traffic accident risks and can also be intensified by sensation-seeking. Other factors such as substance use (alcohol, drugs and “binge drinking”) are also identified as risk factors. Furthermore, cell phone use while driving and ADHD (Attention Deficit Disorder with or without Hyperactivity) also seem to be important risk factors for car accidents. The family environment strongly influences a young person’s driving behavior. Some interventional driving strategies and preventive measures have reduced the risk of traffic accidents among young people, such as the graduated driver licensing program and advertising campaigns. So far, few therapeutic approaches have been implemented. Reason why, we decided to set up an innovative strategy consisting of a therapeutic post-accident group intervention, entitled the ECARR2 protocol, to prevent recurrence among adolescents and young adults identified at risk, taking into account the multiple risk factors.